Assessing the Moisture Transports Associated With Nocturnal Low-Level Jets in Continental South America - Braz, Dejanira Ferreira; Ambrizzi, Tércio; da Rocha, Rosmeri Porfírio; Algarra, Iago; Nieto, Raquel; Gimeno, Luis (Frontiers in Environmental Science, 2021)
Given the crucial role of low-level circulation in convective events, this study presents a climatological characterization of the moisture sources and sinks associated with the occurrence of nocturnal low-level jets (NLLJs) in South America. Six selected NLLJ cores are identified according to the jet index that considers a vertical wind speed shear of the lower troposphere at 00:00 local time (LT). The Lagrangian FLEXible PARTicle (FLEXPART) model was used to provide the outputs for tracking atmospheric air masses to determine the moisture sources and sinks for the NLLJ cores (Argentina, Venezuela, and the regions of Brazil: south—Brazil-S, southeast—Brazil-SE, north—Brazil-N, and northeast—Brazil-NE). The analysis is based on 37 years (1980–2016) of the ERA-Interim reanalysis. We found that the NLLJ index is stronger in the warm periods of a year (austral spring and summer) for the six selected regions. The NLLJ frequency is also higher in the warm months of the year, except in Brazil-NE where it is very frequent in all months. In Brazil-NE, the NLLJ also persists for 8 or more days, while the other NLLJs frequently persist for 1–2 days. The NLLJs occupy a broad low-level layer (from 1000 to 700 hPa) and exhibit a mean speed between 7 and 12 ms–1, which peaks mostly at 900 hPa. The moisture transport for each NLLJ shows that in addition to the intense local moisture sources, the NLLJs in Argentina and Brazil-S receive moisture from the tropical-subtropical South Atlantic Ocean and the Amazon basin, while the tropical-subtropical South Atlantic Ocean is the main moisture source for the NLLJ in Brazil-SE. Both moisture sources and sinks are stronger in the austral summer and fall. The NLLJ in Brazil receives moisture from the tropical South Atlantic (TSA) Ocean, which has weak seasonality. The moisture sources for the NLLJs in Brazil-N and Venezuela come from the tropical North Atlantic (TNA) Ocean in the austral summer and fall, while the TSA Ocean appears as an additional moisture source in the austral winter. This research contributes to improving our understanding of the NLLJs and their role in transporting moisture and controlling precipitation over the continent according to the seasons of a year, helping to improve seasonal climate forecasting.